A new leaf [videorecording (DVD)] - May, Elaine, 1932- (Olive Films, 2012)
Henry Graham is a man with a problem: he has run through his entire inheritance and is completely unequipped to provide for himself. His childhood guardian, Uncle Harry, refuses to give him a dime, so Henry devises a plan with the help of his imaginative butler to make his money the old-fashioned way, he can marry it.